Compact and high‐selectivity microstrip bandpass filter using two‐stage twist‐modified asymmetric split‐ring resonators. Issue 8 (1st April 2015) - Li, Jian; Huang, Yongjun; Wen, Guangjun; Xue, Xiaolin; Song, Jiaming
Abstract : A compact and high frequency selectivity two‐stage microstrip bandpass filter is designed and experimentally demonstrated. Such a kind of filter is composed of two pairs of twist‐modified asymmetric split‐ring resonators (SRRs) to achieve three transmission poles within the passband and four transmission zeros at low and high rejection bands. Sharply out‐of‐band reductions contributing to the high frequency selectivity are obtained by properly detuning the gaps among the SRRs. The measured results show that the proposed filter with dimensions of 0.088 × 0.088 λ 2 has a 3 dB passband of 15.2% centred at 1.98 GHz. This filter can be flexibly integrated in miniaturised radio‐frequency/microwave circuits.